Is Being a Genus? Syrianus’ Criticism of Aristotle - Granieri, Roberto (Phronesis, 2022)
In Metaphysics B 3 Aristotle sets out a famous argument for the thesis that being is not a genus. In his commentary on Metaphysics B, Syrianus criticizes this argument and explains in what sense being is to be regarded as a genus. I reconstruct both Syrianus’ criticisms and his own view. I bring out ways in which they can help us rethink key assumptions of Aristotle’s ontology and shed light both on Syrianus’ critical attitude towards Aristotle and on some of Syrianus’ main views in metaphysics.